A New Approach to the Parameterization of Streamlined Surfaces of the Left Heart and Aorta, Taking into Account the Twisted Structure of Blood Flow - Ivan Beglov; Eugene Talygin; Yaroslav Zharkov; Alexandre Gorodkov (Applied Sciences)
Using the normal dynamic anatomy of the left heart and aorta as an example, it has been shown that the streamlined surfaces of the flow channels in this segment of the circulation can be approximated with sufficient accuracy by the dependences for the streamlines obtained from the exact solution of the basic equations of hydrodynamics for the class of centripetal swirling viscous fluid flows. It has been shown that, in three consecutive segments of the blood channel, from the left atrium to the end of the aorta, at the moment of maximum flow velocity, the geometrical configuration of the channel satisfies the condition of constancy of the product of the longitudinal and the square of the radial coordinate, and the zone of jet initiation is limited by a concave streamlined surface. The curvature of the flow channel axis has no effect on the hydrodynamic structure of the flow, since it is coherent with the directions of the streamlines.